Empowering Patient-Centered Care After Surgery: How Clinical Competence And Leadership Shape Outcomes Through Nurse Engagement - Moch. Ilfan Gunadi; Rian Adi Pamungkas; Nofierni Nofierni (Alta Dharma Publisher, 2026)
Introduction:This study aimed to analyze the impact of Clinical Leadership and Clinical Competence on the implementation of Patient-Centered Care (PCC) post-surgery, mediated by Work Engagement among nurses at RS Islam Jakarta Cempaka Putih. The optimal implementation of PCC remains a major challenge in improving post-surgical healthcare quality, particularly within the context of limited human resources and complex work dynamics. Problems such as low nurse engagement and variations in leadership and clinical skills affect the effectiveness of PCC delivery. Methods:This quantitative research employed a cross-sectional design at RS Islam Jakarta Cempaka Putih, involving 115 nurses selected through a saturated sampling method. Data were collected using a 4-point Likert scale questionnaire and analyzed with SEMPLS software. Ethical approval was granted by the institutional ethics committee, and informed consent was obtained from all participants. Results:The main outcome was the implementation of post-surgical PCC. Findings indicated that Clinical Leadership, Clinical Competence, and Work Engagement significantly influenced PCC implementation when analyzed simultaneously. Clinical Leadership and Clinical Competence had a positive and significant effect on Work Engagement. Furthermore, Clinical Competence and Work Engagement directly improved PCC implementation, while Clinical Leadership did not show a direct significant effect. Work Engagement acted as a key mediator linking Clinical Leadership and Clinical Competence with PCC implementation. Conclusion:This study highlights the critical role of Work Engagement in enhancing the influence of Clinical Leadership and Competence on PCC implementation. Strengthening leadership, developing clinical skills, and fostering engagement among nurses can improve post-surgical care. Future research should adopt longitudinal designs and explore additional factors to deepen understanding and advance healthcare leadership knowledge.